How long is 3 km for a butterfly? Ecological constraints and functional traits explain high mitochondrial genetic diversity between Sicily and the Italian Peninsula. Issue 9 (23rd March 2020) - Scalercio, Stefano; Cini, Alessandro; Menchetti, Mattia; Vodă, Raluca; Bonelli, Simona; Bordoni, Adele; Casacci, Luca Pietro; Dincă, Vlad; Balletto, Emilio; Vila, Roger; Dapporto, Leonardo
Abstract: Populations inhabiting Mediterranean islands often show contrasting genetic lineages, even on islands that were connected to the mainland during glacial maxima. This pattern is generated by forces acting in historical and contemporary times. Understanding these phenomena requires comparative studies integrating genetic structure, functional traits and dispersal constraints. Using as a model the butterfly species living across the Messina strait (3 km wide) separating Sicily from the Italian Peninsula, we aimed to unravel the mechanisms limiting the dispersal of matrilines and generating genetic differentiation across a narrow sea strait. We analysed the mitochondrial COI gene of 84 butterfly species out of 90 documented in Sicily and compared them with populations from the neighbouring southern Italian Peninsula (1, 398 sequences) and from the entire Palaearctic region (8, 093 sequences). For each species, we regressed 13 functional traits and 2 ecological constraints to dispersal (winds experienced at the strait and climatic suitability) against genetic differentiation between Sicily and Italian Peninsula to understand the factors limiting dispersal. More than a third of the species showed different haplogroups across the strait and most of them also represented endemic haplogroups for this island. One fifth of Sicilian populations (and 32.3% of endemic lineages) had their closest relatives in distant areas, instead of the neighbouring Italian Peninsula, which suggests high relictuality. Haplotype diversity was significantly explained by the length of the flight period, an intrinsic phenology trait, while genetic differentiation was explained by both intrinsic traits (wingspan and degree of generalism) and contemporary local constraints (winds experienced at the strait and climatic suitability). A relatively narrow sea strait can produce considerable differentiation among butterfly matrilines and this phenomenon showed a largely deterministic fingerprint. Because of unfavourable winds, populations of the less dispersive Sicilian butterflies tended to differentiate into endemic variants or to maintain relict populations. Understanding these phenomena required the integration of DNA sequences, species traits and physical constraints for a large taxon at continental scale. Future studies may reveal if the patterns here shown for mitochondrial DNA are also reflected in the nuclear genome or, alternatively, are the product of limited female dispersal. Abstract : Island populations often show contrasting genetic lineages, even on less isolated islands. A large fraction of Sicilian butterfly populations show endemic mitochondrial lineages although the Messina strait is only 3 km wide. Genetic differentiation is explained by intrinsic traits (wingspan and generalism) and environmental constraints (wind direction and climatic suitability).